PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE INDEX DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA PERUSAHAAN (Studi pada Perusahaan Manufaktur yang tercatat Di Bursa efek Indonesia Periode 2016-2018) - Taufik Anggara; Dul Muid (Diponegoro Journal of Accounting, 2022)
Analyzing the effect of the corporate governance index, sub-index, and institutional ownership is the essence of this study. This study develops a governance index consisting of 33 indicators to measure the corporate governance index. Institutional ownership as an independent variable on company performance as the dependent variable. While the control variables used are Gearing, Firm Size, Growth Opportunities, Firm Age, Board Ownership, Block Shareholdings. The research population is 93 manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2018 period. Purposive sampling technique was selected and applied as a sampling technique in this study. The results obtained from this study indicate that the corporate governance index,institutional ownership has a significant positive effect on firm performance, and the sub-index has a significant negative effect on firm performance. However, not all elements of the corporate governance index have a significant influence on company performance.